Norwegian pre-service teacher students’ and public health nursing students’ views on health – a qualitative study of students’ perceptions - Turid Kristin Bigum Sundar; Hanna Sargenius; Lisbeth Gravdal Kvarme; Bente Sparboe-Nilsen (International Journal of Qualitative Studies on Health & Well-Being)
Purpose In 2020, the Norwegian school curriculum was revised, introducing a new cross-curricular subject, Public Health, and Life Skills. The curriculum emphasizes collaboration between teachers and the school health service. Subsequently, a research project, Literacies for Health and Life Skills, was initiated at Oslo Metropolitan University. The aim was to develop a new approach to the subject. A part of the research was to explore perceptions about good and poor health among teacher students and public health nursing students. Methods This study has a qualitative design using auto-photography, group discussions and photo-elicitation interviews as methods to explore the students’ views on health. Results A analysis revealed three themes about good health in both student groups: Relaxation and tranquillity, belonging and relations, and enjoyment as important to health. Three themes about poor health emerged in both student groups: The ideal body and self-perception, you are as healthy as you feel, and the best in life is also the worst. The students’ statements were characterized by underlying assumptions about health in society, with a focus on “healthism”. No major differences between the student groups were found. Conclusion This study serves as a step towards increased understanding of health perceptions among future professionals working with children and adolescents.